#RAINMUSTFALL – A THEOLOGICAL REFLECTION ON DROUGHT, THIRST, AND THE WATER OF LIFE - Nadia Marais (Acta Theologica)
This article focuses on the rhetorical interplay between drought, thirst, and the water of life in a time of drought. The negotiation of meaning that occurs in the interaction between Jesus and the Samaritan woman (John 4) reflects the struggle for meaning that occurs when water is rhetorically ambiguous in a time of water scarcity. This paper argues that the theological rhetoric of water is embedded in soteriological imagination, which requires remembering – through the sacrament of baptism – the significance of the giving God who wills human and ecological flourishing.2 Moreover, it is argued that the good news of salvation brings rhetoric and ethics, doctrine and life, into a dynamic communicative process, so that water, as that which is freely given by God, has nothing less than abundant life or ecological and human flourishing as its apparent intended focus.